Strategic Talent Management and Its Impact on Organizational Performance: A Cross-Cultural Analysis - Sulastri, Lilis (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This study explores the impact of strategic talent management on organizational performance through a cross-cultural lens. Utilizing a comprehensive literature review, the research synthesizes existing studies to identify key factors that influence the effectiveness of talent management practices across different cultural contexts. The findings highlight the critical role of aligning talent strategies with organizational goals to enhance performance outcomes. Moreover, the study reveals that cultural nuances significantly affect the implementation and success of these strategies. The research contributes to the existing body of knowledge by providing a nuanced understanding of how strategic talent management can be leveraged for optimal organizational performance in diverse cultural settings. Implications for theory and practice are discussed, emphasizing the need for culturally adaptive talent management frameworks. The study concludes with recommendations for future research and practical applications in global organizations.